Browser-Side Security Vulnerabilities in Healthcare Institutions Using Dynamic Application Security Testing (DAST): A Case Study of RS Mata Makassar - Supriadi Syam; Abdillah SAS; Sahabuddin; Muh. Fadli Fauzi Sahlan (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – Digital transformation has made healthcare websites critical for patient services, yet regional providers in developing economies often face a